Analisis Minat Masyarakat Surabaya Terhadap Udon (Kajian Sosiologi Budaya) - Nur Azizah; Eva Amalijah (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
Abstract. The development of times and technology is increasingly rapid, facilitating the dissemination of information that makes foreign or foreign cultures enter a country. Especially the influence of foreign culture on food makes changes in the taste of foreign cuisine in Indonesian society. Like Japanese-style thick noodles or also called Udon, which are currently also found in many Japanese-style food outlets in Indonesia, especially in Surabaya. The purpose of this study is to describe the interest of the people of Surabaya in Udon. The method in this study uses a quantitative descriptive methode. A method that aims to create an objective picture or description of a research that uses numbers, starting from data collection, interpretation of the data as well as the appearance and results. Sample collection was carried out by distributing questionnaires in the form of online links to 150 respondents regarding the interest of the people of Surabaya in Udon. In this study using Likert scale analysis and Spearman rank correlation. The results obtained from the Likert scale data for the most preferred type of Udon are `Curry Udon` followed by `kake Udon` then `Nabeyaki Udon` with an interpretation rate of 53.16% which means that the respondent's interest in Udon is categorized as "Neutral" (between interest and not interest). The results of the Spearman rank test show that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, in other words that the first question and the second question have a significant correlation, meaning that the respondent has eaten Udon. Keywords: Interest, Udon, Types of Udon. Abstrak. Perkembangan zaman dan teknologi yang semakin pesat, memudahkan penyebaran informasi yang membuat budaya asing masuk ke dalam suatu negara. Terutama pengaruh budaya asing terhadap makanan menjadikan perubahan selera masakan asing pada masyarakat Indonesia. Seperti mie tebal ala jepang atau juga di sebut dengan Udon yang saat ini juga banyak ditemukan pada gerai makanan ala jepang di Indonesia terutama di Surabaya. Tujuan dari penelitian ini mendeskripsikan minat masyarakat Surabaya terhadap Udon. Metode yang digunakan dalam penelitian ini ialah metode deskriptif kuantitatif. Suatu metode yang bertujuan untuk membuat gambaran atau deskripsi pada suatu penelitian secara objektif yang menggunakan angka, mulai dari pengumpulan data, penafsiran terhadap data tersebut serta penampilan dan hasilnya. Pengumpulan sampel dilakukan dengan cara membagikan kuesioner berupa link secara online kepada 150 orang responden mengenai minat masyarakat Surabaya terhadap Udon. Dalam penelitian ini menggunakan analisis skala likert dan korelasi spearman rank. Hasil yang diperoleh data skala likert jenis Udon yang paling disukai adalah “Curry Udon” disusul oleh “kake Udon” lalu “Nabeyaki Udon” dengan skor Interpretasi 53,16 % yang artinya minat responden terhadap Udon dikategorikan “Netral” (di antara minat dan tidak minat). Hasil uji coba spearman rank diketahui analisis Hipotesis nol (Ho) Ditolak dan Hipotesis alternatif (Ha) Diterima dengan kata lain bahwa pertanyaan pertama dengan pertanyaan kedua memiliki korelasi yang signifikan, maka responden tidak hanya tahu tentang Udon tetapi juga pernah makan Udon. Kata kunci: Minat, Udon, Jenis Udon.